Growth factor profile of irradiated human dermal fibroblasts using a serum-free method - Lonergan, Devin M; Mikulec, Anthony A; Hanasono, Matthew M; Kita, Magdalena; Koch, R James (Plastic and reconstructive surgery (1963), 2003)
Radiation therapy for cancer permanently damages tissue in the line of treatment. This study sought to establish a serum-free protocol to evaluate the growth of irradiated fibroblasts and to analyze the levels of basic fibroblast growth factor (bFGF) and transforming growth factor-beta (TGF-beta) compared with normal fibroblasts. One irradiated cell line of human dermal fibroblasts was established from an intraoperative specimen obtained from a patient who had undergone radiation therapy for head and neck cancer. Irradiated and normal fibroblasts were then plated in UltraCULTURE (serum and growth factor free), modified Webber's medium (bFGF 50 ng/ml, insulin-like growth factor 100 ng/ml), and Dulbecco's Modified Eagle Medium with 10% fetal bovine serum (serum with undefined basal growth factors). Irradiated cells were also seeded in UltraCULTURE with 50 and 100 ng/ml of bFGF. Cell counts were performed at 0, 1, 3, 5, and 7 days, and cell supernatants were assayed for bFGF and TGF-beta. Irradiated and normal fibroblasts exhibited stronger growth in modified Webber's medium than in Dulbecco's Modified Eagle Medium with 10% fetal bovine serum. Growth of irradiated fibroblasts under bFGF modulation was similar to their growth in Webber's medium. Furthermore, irradiated fibroblasts remained viable in a serum-free and growth factor-free environment for at least 7 days; however, their growth and autocrine growth factor production was less than that of normal cells. This confirms the results of previous studies suggesting that cells from irradiated tissue undergo cellular changes. This study provides an effective model for the first-line evaluation of agents to improve wound healing, and it helps to establish standard levels of bFGF and TGF-beta production for irradiated fibroblasts.